FORMULATION OF FISH CYPSELURUS OPHISTHOPUS AND SQUID THYSANOTEUTHIS RHOMBUS BARS AS A CONVENIENT FOOD - Juntilla, Ursina S; Delan, Gloria G; Cuñado, Venerando D (Journal of Agriculture and Technology Management; Tropical Technology Journal Volume 11 No. 1-2, 2008, 2008)
The fish were cleaned, filleted and minced. Constant weight of minced fish meat were mixed in varying amount of minced squid meat such as 50%, 75%, 100% and pure minced fish as control sample. The ingredients were added and the mixtures were chilled. The products were sliced into bars, fried prior to serving. The most acceptable formulation was determined through sensory evaluation by a group of 50 consumer–type panelists. The product was subjected to proximate composition and storage study at refrigerated condition (8 – 100C) with sensory, microbiological and chemical evaluations conducted. Data gathered were treated statistically using ANOVA at 5% level of significance and simple correlation (R).Based on ANOVA, the samples showed significant difference in all the quality attributes considered. Direct relationship was obtained between TVB-N and TPC when correlated. The most acceptable formulation was the product with 100% squid meat. It has a good blend of taste between fish and that of squid. The product has a general acceptability rating of 5 which means “like very much” on 5- point Hedonic scale. On proximate composition, the product has 63.3% moisture, 2.68% ash, 15.4 protein, 3.88% fat, 14.7% carbohydrates and a total calorie content of 155 kcal / 100 g sample. The shelf-life of the product was about one month at refrigerated condition with total plate count (TPC) of 10 x 10 8 cfu/g sample and a TVBN of 112 mg TVB-N/ 100 gram sample. On descriptive sensory test, the odor of the product became foul with an equivalent rating of 1.5 on the 5 Hedonic score card.